Sistem Informasi Inventory Outsole Berbasis Desktop Pada PT Pratama Abadi Industri - Jihad Fadillah, Hafis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Inventory is a stock of materials used to facilitate production or to satisfy customers, which includes raw materials, in-process goods and finished goods. Inventory is goods that are stored for use or sale in the future or period. Outsole inventory data processing in this company still uses a manual system in the form of a piece of paper to record outsole inventory data. This system is less effective and efficient so there is still a lot of data that often has discrepancies so that the data reported is less accurate. Therefore, companies need an outsole inventory system that can assist in processing data on incoming and outgoing goods so that the data reported is accurate. With this outsole inventory system, it can help companies manage data processing of incoming goods and outgoing goods quickly, easily, effectively and efficiently. In making the inventory system, the outsole is designed in a desktop display which is useful for making it easier for computer or laptop users to manage data so that they can produce a report that is fast, precise and accurate.